A Review of the Single Phase Photovoltaic Module Integrated Converter Topologies With Three Different DC Link Configurations - Li, Q.; Wolfs, Peter (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2008)
The annual world photovoltaic (PV) cell/module production is growing at almost an exponential rate and has reached 1727 MW in 2005. Building integrated PV (BIPV) projects are emerging as the strongest part of the PV market and grid interactive inverters are a key component in determining the total systemcost. Module integrated converter (MIC) technology has become a global trend in grid interactive PV applications and may assist in driving down the balance of system costs to secure an improved total system cost. This paper concentrates on the topology study of the PV MICs in the power range below 500 W and covers most topologies recently proposed for MIC applications. The MIC topologies are classified into three different arrangements based on the dc link configurations. A systematic discussion is also provided at the end of the paper that focuses on the major advantages anddisadvantages of each MIC arrangement. These are considered in detail and will provide a useful framework and point of reference for the next generation MIC designs and applications.